2018
DOI: 10.1186/s12883-018-1069-5
|View full text |Cite
|
Sign up to set email alerts
|

Axonal chronic injury in treatment-naïve HIV+ adults with asymptomatic neurocognitive impairment and its relationship with clinical variables and cognitive status

Abstract: BackgroundHIV is a neurotropic virus, and it can bring about neurodegeneration and may even result in cognitive impairments. The precise mechanism of HIV-associated white matter (WM) injury is unknown. The effects of multiple clinical contributors on WM impairments and the relationship between the WM alterations and cognitive performance merit further investigation.MethodsDiffusion tensor imaging (DTI) was performed in 20 antiretroviral-naïve HIV-positive asymptomatic neurocognitive impairment (ANI) adults and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 46 publications
(72 reference statements)
4
35
0
Order By: Relevance
“…The findings from our current study are consistent with numerous studies that documented elevated diffusivity in widespread white matter regions (Chang et al 2008; Gongvatana et al 2009; Pfefferbaum et al 2009;Masters and Ances 2014; Nir et al 2014; O’Connor et al 2017), and most frequently in the corpus callosum, of HIV+ patients (Masters and Ances 2014; O’Connor et al 2017). Our findings of elevated mean diffusivity, primarily due to elevated AD, with normal FA, in our HIV+ participants are consistent with prior reports (Pfefferbaum et al 2009; Li et al 2018). However, lower FA and higher RD in HIV+ compared to SN participants were also reported by others (Leite et al 2013; Underwood et al 2017).…”
Section: Discussionsupporting
confidence: 93%
“…The findings from our current study are consistent with numerous studies that documented elevated diffusivity in widespread white matter regions (Chang et al 2008; Gongvatana et al 2009; Pfefferbaum et al 2009;Masters and Ances 2014; Nir et al 2014; O’Connor et al 2017), and most frequently in the corpus callosum, of HIV+ patients (Masters and Ances 2014; O’Connor et al 2017). Our findings of elevated mean diffusivity, primarily due to elevated AD, with normal FA, in our HIV+ participants are consistent with prior reports (Pfefferbaum et al 2009; Li et al 2018). However, lower FA and higher RD in HIV+ compared to SN participants were also reported by others (Leite et al 2013; Underwood et al 2017).…”
Section: Discussionsupporting
confidence: 93%
“…Myelin damage has been found in central white matter in the pre-antiretroviral therapy era (Gray et al 1992). Like Li et al (2018), we found that the HIV group had increased MD in the corpus callosum and corona radiata among other regions. It has been suggested that these regions, being periventricular, are more vulnerable to viral invasion and neuro-inflammation in early infection when HIV infiltrates the CSF and by extension the white matter tracts (Li et al 2018; Ragin et al 2015).…”
Section: Discussionsupporting
confidence: 83%
“…Like Li et al (2018), we found that the HIV group had increased MD in the corpus callosum and corona radiata among other regions. It has been suggested that these regions, being periventricular, are more vulnerable to viral invasion and neuro-inflammation in early infection when HIV infiltrates the CSF and by extension the white matter tracts (Li et al 2018; Ragin et al 2015). A meta-analysis by O’Connor et al (2017), while only revealing a small reduction in FA in HIV, with high study heterogeneity, revealed a significant increase in MD in HIV.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Following initial infection, HIV crosses the blood-brain-barrier and can produce diffuse neuropathology, affecting both cortical and subcortical grey matter as well as white matter tracts linking different brain regions (Janssen et al 2015;van Zoest et al 2017;O'Connor et al 2018;Li et al 2018;Oh et al 2018). This non-localised pattern of infection may explain why HAND is characterised by a broad range of possible impairments (Woods et al 2009).…”
Section: Discussionmentioning
confidence: 99%